“Material concreto para el desarrollo de la psicomotricidad fina en los procesos de aprendizaje de los niños de Educación Inicial” - Núñez Luzpa, Alicia Narely (2024)
As a preceding fact, the problem raised in this project about the lack of fine psychomotor skills, and how this has significantly affected the different learning processes of the children of the educational institutions located in the parish of Angamarca - Canton Pujilí, Province of Cotopaxi. The objective was to elaborate a didactic guide through activities that require the use of concrete material for the enhancement of fine psychomotor skills in the children of the educational units located in the parish of Angamarca in the school year 2024-2025. In this research the constructivist pedagogical approach was used since through it a transcendental learning process is obtained, because students build their own knowledge through interaction with their environment, which is why this project is proposed with the theme "Concrete material for the development of fine psychomotor skills in the learning processes of children in early childhood education", which aims to solve a number of difficulties that students have. The present proposal was correctly evaluated and validated by three experts and two users who unanimously approved it, which allowed concluding that, through early interventions and activities with the use of concrete material, it facilitates the acquisition of new knowledge, while developing their fine psychomotor skills in a dynamic and innovative way.